Intensifikasi Karakter Profil Pelajar Pancasila di MI Syu’batul Kholafiyah - Sastri Defi; Muhammad Hifdil Islam; Choerul Anwar Badruttamam (Departement of Mathematics Education, 2023)
The purpose of education is not only the process of humanization, but also efforts to help, and develop all the opportunities they can and also for success in the life of the present world and the world in the future. The research method used is a qualitative descriptive method, this research was conducted for natural purposes. Natural goals are personalities that grow as the facts are, not manipulated by researchers and the presence of researchers. Research conducted Field research and data found by researchers using interview documentation with curriculum experts at MI Syu’batul Kholafiyah Jatiurip. The results of this study can be carried out by direct observation to see the strengthening of the Pancasila character profile of MI Syu’batul Kholafiyah Jatiurip students. The Ministry of Education and Culture emphasizes the importance of character building through the 2020-2035 Indonesian Education Plan, one of the slides explaining that superior human resources are lifelong learners with global skills and behaviors that are in line with the noble qualities of Pancasila. The development of superior human resources must be comprehensive and not only focus on cognitive skills. Character education is a method of activity that is carried out using all resources and conscious and periodic work to guide students. The values ​​of personality thought that are internalized in the research are religion, patriotism, intelligence, accountability, obedience, independence. The profile of Pancasila aims to shape Indonesian students to be permanent education. Pancasila competence is an outline of the ability of students with personality in the same direction as Pancasila quality. Pancasila students have six virtues, namely faith, piety to God Almighty, international diversity, mutual cooperation, independence, responsive thinking and noble character.